Representation of Nationalism in The Kubro Art Performed by The Seven Angel Kubro Art Group - Wahyuni, Dwi; Harini; Selly Rizki Yanita (BRIN Publishing (Penerbit BRIN), 2025)
The development of popular culture lately has an impact on local culture which is starting to be abandoned, especially by the younger generation. Like kesenian Kubro in Ngasinan Village, Purworejo, which was abandoned because there was no longer public enthusiasm for that art. Kubro in Ngasinan Village has been preserved again by Grup Kesenian Kubro Tujuh Bidadari by combining Kubro with dangdut rhythms to suit the tastes of the community. This effort is a big thing in preserving local culture. Especially with the involvement of children who are the nation's next generation in this effort. Thus, Kubro can be a representation of nationalism through regional arts that are adapted to the times without losing the identity of the art. In this study, visual and non-visual signs that represent nationalism will be analyzed. The method used in this study is a qualitative descriptive method with a semiological approach. Based on the results of the analysis, there are representations of nationalism found in dance moves, the costumes of dancers, and Kubro’s song lyrics in Purworejo Regency. Based on the results of the analysis, it is hoped that the main purpose of this art as an effort to preserve a local culture that represents nationalism as well as entertainment for the community can be fulfilled.